The plane piston problem with weak gravitational field in a dusty gas - J.P. Chaudhary; S.D. Ram; L.P. Singh (Elsevier B.V., 2018)
In the present paper, the nature of a plane piston moving with constant velocity in a gas with dust particles in the presence of weak gravitational field is analyzed by using a combination of two methods, viz., perturbation method and similarity transformation. In perturbation method the physical variables are expanded as a series of small parameter. The zeroth order result represents the uniform flow which is affected by dust particles of the mixture without gravity. The first order result shows the consequence of applied gravity in a dusty gas. The effect of dust particles present in the gas and applied gravity on the distribution of flow variables has been discussed for the case of weak and strong shock wave. The structure of the shock wave front is also discussed.
Keywords: Dusty gas Weak shock Strong shock Perturbation method